A critical analysis of modern painting in the Philippines today - Ledesma, Purita (Kalaw) 1914- (1955)
The author aimed to help the Filipino public understand modern painting in the Philippines today by analyzing the following: general characteristics of modern painting by studying the materials and techniques used, subject matter, approach, color, style, schools of thought, critics and the reaction of the audience; specific characteristics by studying the individual painters; the influence which modern painting in the Philippines has undergone; and lastly, the aspects of modern painting which can be of benefit to society.